Money demand in Guyana - Egoumé-Bossogo, Philippe ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2000)
Analyzes broad money demand in Guyana from January 1990 to September 1999. Develops a stable error-correction model based on a long-run cointegrating vector of money demand.